Assessing university student perceptions and comprehension of climate change (Portugal, Mexico and Mozambique) - Morgado, Fernando (2018)
Higher education system has a critical role to play in educating environmentally aware and participant citizens about global climate change (CC). And, as shown by the 21st Conference of the Parties of the UN Convention on Climate Change – COP 21, held in Paris in December 2015, there is still a path to be followed regarding the role played by universities in the negotiations and in influencing decision-making on a matter of such global importance. The purpose of this first study conducted within Portuguese (Europe), Mexican (Spanish-speaking North America University) and Mozambican (Africa) universities is to investigate higher education system students’ perceptions on CC. Design/methodology/approach The data were collected through a questionnaire aiming at characterising students from the socio-demography, and from their perceptions, motivations, attitudes and knowledge relating to the topic of CC. Statistical analysis was used to compare and characterise the three national groups under study. Findings This study did not show significant perception differences among the analysed subsamples, although there was a tendency for Mexican students to express lesser belief that CC was happening, and for Mozambicans to show a greater belief in CC issues and motivation to mitigate its effects which may be related to the specifics contexts. The results show that relevant differences among nationalities mostly concerned the magnitude of choices (e.g. most respondents of each nationality expressed interest in CC issues, but the magnitude of this expression differed according to nationality). The principal component analysis (second and third components) clearly embodied nationality profiles (discussed in the context of different cultures, educational structures and CC impacts). Research limitations/implications Further research is warranted to understand the integration of CC into higher education curriculum to improve and target educational efforts to suit students’ needs. Practical implications How CC perceptions vary cross-nationally and how research studies that examine the integration of CC into higher education curriculum are areas for which more research is needed. Originality/value The results highlight the importance of socio-cultural dimensions of each country in relation to the understanding or perception of CC issues, namely, in what concerns aspects related with gender roles, age, active learning and citizenship. This study’s data evidenced that despite the surveyed students being familiarized with CC phenomena, this knowledge does not translate necessarily into concrete mitigation practices and behaviours.